2018
DOI: 10.1111/tpj.14076
|View full text |Cite
|
Sign up to set email alerts
|

Successful floral‐dipping transformation of post‐anthesis lisianthus (Eustoma grandiflorum) flowers

Abstract: The adaptation of the Agrobacterium-mediated floral-dipping technique is limited, to date, to a small number of plants. In this paper, we present the efficient transformation of one of the leading plants in the cut flower industry, lisianthus (Eustoma grandiflorum). This method is approximately 18 months shorter than the known tissue culture-based transformation. The Excalibur Pink cultivar and two additional breeding lines, X-1042 and X-2541, were transformed using three different marker genes (benzyl alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…However, neither of them could get transformants from crossing when inoculated plants served as pollen donors and non-inoculated plants served as pollen recipients [21, 23]. Recently, it was reported that prairie gentian ( Eustoma grandifloru ; also called lisianthus) was successfully transformed via the floral dip method at a post-anthesis stage when ovaries were partially sealed, while in these flowers a stylar channel remained open [18]. Another study recently reported tomato transformation by floral bud injection [17], another approach to providing Agrobacterium with access to ovules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither of them could get transformants from crossing when inoculated plants served as pollen donors and non-inoculated plants served as pollen recipients [21, 23]. Recently, it was reported that prairie gentian ( Eustoma grandifloru ; also called lisianthus) was successfully transformed via the floral dip method at a post-anthesis stage when ovaries were partially sealed, while in these flowers a stylar channel remained open [18]. Another study recently reported tomato transformation by floral bud injection [17], another approach to providing Agrobacterium with access to ovules.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to tissue culture, such methods are typically less time-consuming and labor-intensive [15]. Confirmed successes with in planta transformation had previously been limited to plants in the Brassicaceae, but successes have now been reported for Eustoma grandiflorum , Setaria viridis and Solanum lycopersicum [1618]. Pakchoi ( Brassica rapa ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Plants were hand pollinated and the seeds were harvested after 2 months. Seedlings were transferred to selection media containing 50 mg/L kanamycin 1 month after germination (Fang et al, 2018).…”
Section: Floral Dipping Transformationmentioning
confidence: 99%
“…The lisianthus cultivar "Excalibur Pink" was chosen for transformations due to its vigor and the recent efficient and relatively fast flower-dipping transformation method developed for this cultivar (Fang et al, 2018). "Excalibur Pink" plants were transformed with both AroG* and C. breweri BEAT constructs (Figure 2(A)) and screened as described in Fang et al (2018). The putative transgenic plants were then analyzed for genomic integration, expression of the transgene, and for AroG* protein accumulation (Figure 2(B)-(D)).…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation